Pesan-pesan Dakwah dalam Bahasa Tutur - Hikmat, Hikmat (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2015)
Forwarding of The daâ€™wah messagesÂ in oral language. Oral language in this context isÂ transmitted, trasacted and transformated from relevan values. Even if the message of daâ€™wah in oral language is culture frame that eksist in community, but its posite not outsideÂ of principles: qulan sadidan, Balighan, maâ€™rufan, kariman, layyinan, dab qoulan maysuran, that the message od daâ€™wah can be manual by people danÂ followed it, because daâ€™I is a availableÂ person for people followed it all.